2018
DOI: 10.6061/clinics/2018/e548s
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress: therapeutic approaches for cervical cancer treatment

Abstract: OBJECTIVES: Oxidative stress results from an imbalance between the generation and elimination of oxidant species. This condition may result in DNA, RNA and protein damage, leading to the accumulation of genetic alterations that can favor malignant transformation. Persistent infection with high-risk human papillomavirus types is associated with inflammatory responses and reactive oxygen species production. In this context, oxidative stress, chronic inflammation and high-risk human papillomavirus can act in a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 166 publications
0
24
0
Order By: Relevance
“…contribute to the production of reactive oxygen/nitrogen species [18], which ultimately results in oxidative stress induced damages associated with nucleic acid and protein, thereby leading to cancer malignancy. In cervical cancer, persistent HPV infection and the interaction of HPV oncoprotein components E6 and E7 with tumor suppressor factors and cell cycle regulators lead to the production of ROS followed by cell transformation process [15]. Further numerous antioxidant proteins were found to be deregulated in HPV-associated penile and cervical carcinomas by modulating the accumulation of oxygen species.…”
Section: Introductionmentioning
confidence: 99%
“…contribute to the production of reactive oxygen/nitrogen species [18], which ultimately results in oxidative stress induced damages associated with nucleic acid and protein, thereby leading to cancer malignancy. In cervical cancer, persistent HPV infection and the interaction of HPV oncoprotein components E6 and E7 with tumor suppressor factors and cell cycle regulators lead to the production of ROS followed by cell transformation process [15]. Further numerous antioxidant proteins were found to be deregulated in HPV-associated penile and cervical carcinomas by modulating the accumulation of oxygen species.…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro studies have shown that resveratrol has antitumor, antioxidant, anti-inflammatory, cardioprotective and antiplatelet activity, and glycosylated stilbenes have antifungal and antioxidant effects (Flamini et al, 2013). Studies conducted with resveratrol showed that it improves the effectiveness of cisplatin and doxorubicin chemotherapy, suggesting that it can be used in cervical cancer treatment (Silva et al, 2018).…”
Section: Polyphenols Analysismentioning
confidence: 99%
“…In inflammation NF-kB is a pleiotropic transcription factor that regulates the expression of genes like those for chemokines, cytokines, cell adhesion molecules, growth factors, antioxidant enzymes, iNOS, and others (Silva et al, 2018). NO produced under these conditions is an effector molecule that may have beneficial or harmful effects.…”
Section: In Vivo Antioxidant Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, dietary polyphenols possess an ability to modulate biological states associated with OS and chronic inflammation that may be primary contributors to different types of cancers including cervical, ovarian and breast cancer. Various studies have also demonstrated the dynamic role of polyphenols in the suppression of inflammation related to cancer development [ 18 ]. For instance, a study in Mus musculus showed the beneficiary effects of GTPs such as epigallocatechin gallate (EGCG) on ultraviolet based (UVB) induced skin tumors.…”
Section: Introductionmentioning
confidence: 99%